Statistics anxiety and achievement in a statistics course among psychology students - Abd Hamid, Harris Shah; Sulaiman, Muhamad Karimi (Behavioral Science Research Institute, Srinakharinwirot University, 2014)
Learning of statistics presents a challenge to psychology students whose background in mathematics is not strong. The percentage of students who failed Statistics course at the Department of Psychology in one university in Malaysia is of concern. A survey that included a measure of statistics anxiety was conducted at the beginning of a semester among students taking a statistics course. Performance measures included a basic mathematic review quiz, continuous assessment mark, final examination marks, and total marks. The course was divided into three sections, all taught by the same instructor. Scores from 139 students were used in the analysis. Statistics anxiety and attitude towards statistics are not significantly correlated and both are not related to the total marks. The mathematics quiz score is a significant predictor of total marks. The instrument for measuring pre-course mathematics ability could be used in class as part of the teaching strategy to improve students‟ learning experience.